2008
DOI: 10.1038/ki.2008.103
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cytochrome P450s metabolize aristolochic acid and reduce its kidney toxicity

Abstract: Cytochrome P450s metabolize the naturally occurring nephrotoxin aristolochic acid. Using liver-specific cytochrome P450 reductase-null mice we found that a low but lethal dose of aristolochic acid I was ineffective in wild-type mice. Induction of hepatic CYP1A by 3-methylcholanthrene pretreatment markedly increased the survival rate of wild type mice given higher doses and these mice were protected from aristolochic acid I-induced renal injury. Clearance of aristolochic acid I in null mice was slower compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 37 publications
5
72
0
Order By: Relevance
“…Because the physiological counteranions and gradients driving Oat2 transport have not been identified, it is unclear whether it functions in a secretory or reabsorptive mode. This transporter is also highly expressed in liver, the primary site of AA-I detoxification (Xiao et al, 2008). Hepatic Oat2 is localized to the basolateral (sinusoidal) membrane (Simonson et al, 1994), where it could conceivably mediate influx of AA-I or efflux of its metabolites, such as AA-Ia.…”
Section: Discussionmentioning
confidence: 99%
“…Because the physiological counteranions and gradients driving Oat2 transport have not been identified, it is unclear whether it functions in a secretory or reabsorptive mode. This transporter is also highly expressed in liver, the primary site of AA-I detoxification (Xiao et al, 2008). Hepatic Oat2 is localized to the basolateral (sinusoidal) membrane (Simonson et al, 1994), where it could conceivably mediate influx of AA-I or efflux of its metabolites, such as AA-Ia.…”
Section: Discussionmentioning
confidence: 99%
“…, oxidative) conditions both CYP enzymes are able to O -demethylate AAI to a detoxification metabolite, 8-hydroxyaristolochic acid I (aristolochic acid Ia, AAIa; Figure 2). Under these (aerobic) conditions, AAI behaves as a classical substrate of human CYP1A1 and 1A2, where one oxygen atom is utilized for O -demethylation of AAI to form AAIa [46,47,62,86,87,89,91,92,93]. These experimental results strongly suggest that, besides CYP1A1 and 1A2 expression levels, the oxygen level in tissues affects the balance between AAI nitroreductive activation and oxidative detoxication by these CYPs in vivo [47,62,86,87,89].…”
Section: Cytosolic Nad(p)h:quinone Oxidoreductase (Nqo1) and Micromentioning
confidence: 99%
“…Previous studies have demonstrated that most of the toxins are physiologically transported and metabolized in the organs (e.g., liver, kidneys) by some specific enzyme/protein, including P-glycoprotein [7], cytochrome P450 (CYP1A1) [8], NAD(P)H quinone oxidoreductase 1 (NQO1) [9] and glutathione S-transferase (GST) [10]. The expression and function of these enzymes/proteins may influence drug metabolism and transport [9,11,12].…”
mentioning
confidence: 99%